1982
DOI: 10.1126/science.6171885
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Antigen Expression by Primate T Cells

Abstract: showed MLV particles with a weightaverage diameter of 152 nm as compared to the 232 nm found in HN buffer. This represents a water loss of 67 percent in the MLV and an increase in particle density to 1.0472 g/cm3, as compared to the 1.0154 g/cm3 assumed for the original particles.The particle size distribution data for the SUV particles are believed to be reasonably accurate even though no correction for the osmotic effect of the sucrose-buffer mixture was used in the measurement. The osmotic activity for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
28
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 16 publications
11
28
0
1
Order By: Relevance
“…Previous reports had claimed that the CD4/CD8 ratio in macaques was inverted (2,3,22) and these findings raised concerns about similarities between immune systems in these species. When CD4/CD8 ratios were calculated using CD8 T-cell counts defined by the CD8ϩ alone, our values were around the value of 0.75-1.3.…”
Section: Discussionmentioning
confidence: 82%
“…Previous reports had claimed that the CD4/CD8 ratio in macaques was inverted (2,3,22) and these findings raised concerns about similarities between immune systems in these species. When CD4/CD8 ratios were calculated using CD8 T-cell counts defined by the CD8ϩ alone, our values were around the value of 0.75-1.3.…”
Section: Discussionmentioning
confidence: 82%
“…Given that T11 is more phylogenetically conserved than any known human T-lineage structure (12), appears earliest during intrathymic ontogeny, and, unlike the Ti a and ,B subunits (13), is monomorphic, thus containing no variable domains, it is possible that T11 represents a primitive T-cell surface activation molecule. Primary sequence information might suggest a mechanism by which T11 mediates signal transduction.…”
mentioning
confidence: 99%
“…Most antibodies of the same type showed similar reactivity, but a few of them varied in reactivity with the panel cells. We did not examine cell lines of gorillas and orangutans, but the epitope defined by H-45 appeared to be human-specific, because H-45 did not react with a T-cell line of a chimpanzee, which is known to express T-cell antigens that cross-react with those of humans (8). With these panel cell lines, the reactivity of antibodies H-Cl and H-44 of the H-31-type and H-45 of the HIEI-type was different from that of other H-31-type and HIEI-type antibodies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, well-defined monoclonal antibodies to human major histocompatibility antigens (4) and human T-cell markers (8) have also been used for phylogenetic studies on primates. Haynes et al (8) showed that the antigenic determinants of the SRBC-receptor, but not the determinants of the other T-cell subset marker molecules, have been highly conserved during primate evolution, and that human, gorilla, and chimpanzee T cells have identical reactivity with the monoclonal antibodies to human T-cell subset antigens.…”
mentioning
confidence: 99%